CLINICAL AND BIOCHEMICAL INDICATORS IN WHITE RATS IN THE TREATMENT OF EXPERIMENTAL GENERALIZED PARODONTITIS - Yu.I. Silenko; M.V. Khrebor; Y.M. Silenko; O.A. Pisarenko (Український стоматологічний альманах)
A number of scientists put forward and confirmed the assumption of the presence in the body of biological regulators, polypeptides, carrying out the transfer of information necessary for the functioning, development and interaction of cell populations. The problem of studying the mechanism of action and clinical application of polypeptides is key in modern medicine.